1995
DOI: 10.1086/176425
|View full text |Cite
|
Sign up to set email alerts
|

Multiwavelength Energy Distributions and Bolometric Luminosities of the 12 Micron Galaxy Sample

Abstract: Aperture photometry from our own observations and the literature is presented for the 12 µm Galaxies in the near infrared J, H and K bands and, in some cases, in the L band. These data are corrected to "total" near-infrared magnitudes, (with a typical uncertainty of 0.3 magnitudes) for a direct comparison with our IRAS fluxes which apply to the entire galaxy. The corrected data are used to derive integrated total NIR and FIR luminosities. We then combine these with blue photometry and an estimate of the flux c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
223
1
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(250 citation statements)
references
References 30 publications
25
223
1
1
Order By: Relevance
“…2 http://www.cfht.hawaii.edu/~arnouts/lephare.html nosity dependence similar to the SEDs of the libraries proposed by Chary & Elbaz (2001) and Lagache et al (2004). In this scheme, the monochromatic luminosity at any given IR wavelength is linked to L IR by a monotonic relation, similar to the correlations that have been observed between the mid-IR emission and the total IR luminosity of galaxies in the local Universe (e.g., Spinoglio et al 1995;Chary & Elbaz 2001;Takeuchi et al 2003;Treyer et al 2010;Goto et al 2011). In this way, a 24 µm flux density observed at a given redshift is associated to a unique L IR .…”
Section: The Infrared Luminositysupporting
confidence: 67%
“…2 http://www.cfht.hawaii.edu/~arnouts/lephare.html nosity dependence similar to the SEDs of the libraries proposed by Chary & Elbaz (2001) and Lagache et al (2004). In this scheme, the monochromatic luminosity at any given IR wavelength is linked to L IR by a monotonic relation, similar to the correlations that have been observed between the mid-IR emission and the total IR luminosity of galaxies in the local Universe (e.g., Spinoglio et al 1995;Chary & Elbaz 2001;Takeuchi et al 2003;Treyer et al 2010;Goto et al 2011). In this way, a 24 µm flux density observed at a given redshift is associated to a unique L IR .…”
Section: The Infrared Luminositysupporting
confidence: 67%
“…This means that the selection in the MIR affects the result only very slightly, and the sample properties are controlled by the FIR. It is a clear contrast to the sample of Spinoglio et al (1995) which was 12-µm selected: the present sample consists of more quiescent, normal galaxies than theirs. A full treatment including the upper-limit sample will be presented elsewhere (Takeuchi et al 2004, in preparation).…”
Section: Iras Samplecontrasting
confidence: 58%
“…Based on their 12-µm sample of galaxies, Spinoglio et al (1995) made a pioneering study to examine various correlations between flux densities from near-IR (NIR) to far-IR (FIR), and presented useful diagnostics for Seyferts and normal galaxies on color-color diagrams. They also found that the 12-µm Appendices are only available in electronic form at http://www.edpsciences.org…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the 24 μm-selected sources lies at z < 1 and the distribution of 350 μm-selected sources peaks at z ∼ 1.5. Another possible explanation is that fainter sources lies near z = 1 and are thus selected at the 12 μm rest-frame, which is a very good estimator of the infrared bolometric luminosity according to Spinoglio et al (1995).…”
Section: Accuracy Of the Stacking Counts Methods On Blastmentioning
confidence: 99%